AQA Mathematics for GCSE. Teacher's book. Foundation. Linear 1 - Thornton, Margaret, 1938-; Haighton, June. (Cheltenham : Nelson Thornes, 2006)
Blends (print and electronic) GCSE course for the AQA linear specification. This book aims to deliver: 'stripped down' pupil books, comprehensive teacher books, and easy-to use ICT components (E-M@ths CD-ROM, Teacher book CD-ROM, E-M@ths online and Test and Assessment) which link seamlessly with the print material.
GCSE.
Foundation stage.
Keywords: Mathematics -- Study and teaching (Secondary) -- Great Britain